1987
DOI: 10.1002/eji.1830170523
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of Ia‐like antigens on tumor cells of regressing but not of progressing Rous sarcomas

Abstract: Unlike many other tumors, experimentally induced Rous sarcomas in chickens have a definite tendency to regress spontaneously. Regression is under genetic control, but it is immunologically mediated although the target antigens that stimulate an immune response are unknown. Tumor cells in regressing sarcomas were found to express class II major histocompatibility complex (Ia-like) antigens while tumor cells from progressing sarcomas were negative. This suggests that the induction of Ia-like antigen expression h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…In addition, MHC class II antigens can be demonstrated on malignant cells whereas they are not present on their normal counterparts [4,22,23]. A number of reports have demonstrated that interferon y can induce or angment the expression of MHC class II antigens on tumor cells [1,16,23,30]. Studies on the level of MHC class II antigens on macrophages in tumor-bearing animals have indicated that the anti-tumor response results not only in a local but also in a widespread systemic increase in MHC class Il antigen expression by macrophages [ l 2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MHC class II antigens can be demonstrated on malignant cells whereas they are not present on their normal counterparts [4,22,23]. A number of reports have demonstrated that interferon y can induce or angment the expression of MHC class II antigens on tumor cells [1,16,23,30]. Studies on the level of MHC class II antigens on macrophages in tumor-bearing animals have indicated that the anti-tumor response results not only in a local but also in a widespread systemic increase in MHC class Il antigen expression by macrophages [ l 2].…”
Section: Introductionmentioning
confidence: 99%
“…Our experiments disclosed that circulating lymphocytes are very important in tbe immune process, but, in our case, may not reflect the course of progression or regression of RSV-induced tumours. Tbe change in the composition of infiltrating subpopulations of lymphoid cells is a constant occurrence in the tumour [5]. These changes and the role of these infiltrating cells in the regression process as well as the observed changes in the frequency of B-L + cells in PBL are under furtber analysis.…”
Section: Discussionmentioning
confidence: 99%
“…RSVinduced tumours progress [4]. Tumour cells in regressing sarcomas were found to be positive for MHC class II antigens, while cells in progressitig sarcomas were negative, suggesting a role Tor class II antigen in immunologically mediated regression [5], To analyse Ihis phcnoinenon further we followed the percentages v<^ CD4*. CD8' and B-L^ cells in PBL from tutnourbearing cbickens of botb lines.…”
mentioning
confidence: 99%
“…In chickens of the line CB the tumours regress and in line CC the tumours progress (Plachy et al 1977;Plachy 1988). Tumour cells in regressing sarcomas were found to be positive for B-L (class 11) antigens while tumour cells in progressing sarcomas were negative, suggesting a role for B-L antigens in immunologically mediated regression (Powell et al 1987).…”
mentioning
confidence: 98%